Cardiac regeneration following cryoinjury in the adult zebrafish targets a maturation-specific biomechanical remodeling program. Issue 1 (December 2018) - Yu, Joseph; Sarathchandra, Padmini; Chester, Adrian; Yacoub, Magdi; Brand, Thomas; Butcher, Jonathan
Abstract Cardiac regeneration post-injury is a tantalizing feature of many lower vertebrates such as fishes and urodeles, but absent in adult humans. Restoration of pumping function is a key endpoint of cardiac regeneration, but very little is known about the biomechanical remodeling process. Here, we quantify and compare the evolution of cellular composition and mechanical stiffness of the zebrafish ventricular myocardium during maturation and following cryoinjury during regeneration to better understand the dynamics of biomechanical remodeling during these two processes. With increasing age, normal myocardial trabecular density and cardiomyocyte fraction increased, while non-myocyte cell fractions decreased. Cell density remained constant during maturation. Cardiomyocyte sarcomeres shortened to a minimum reached at 7.5 months of age, but lengthened with additional age. Concomitantly, ventricular wall stiffness increased up until 7.5 months before plateauing with additional age. Endothelial, myofibroblast/smooth muscle, and cardiomyocyte cell fractions were disrupted following cryoinjury, but were progressively restored to age-specific natural norms by 35 days post infarct (DPI). Infarcted myocardium stiffened immediately following cryoinjury and was a 100-fold greater than non-infarcted tissue by 3 DPI. By 14 DPI, stiffness of the infarcted myocardium had fallen below that of 0 DPI and had completely normalized by 35 DPI. Interestingly, cardiomyocyte sarcomere length increased until 14 DPI, but subsequently shortened to lengths below age-specific natural norms, indicating recovery from a volume overloaded condition. These observations are consistent with the view that regenerating myocardium requires biomechanical stimulation (e.g. strain) to rescue from a volume overloaded condition. Intriguingly, the biomechanical progression of the infarcted adult myocardial wall mirrors that of normal remodeling during aging. The biomechanical progression of the infarcted myocardium targets the values of age-specific norms despite a large divergence in initial conditions. These findings identify a novel biomechanical control of heart regeneration that may orchestrate cellular and tissue level remodeling responses.